Music theory : problems and practices in the Middle Ages and Renaissance - Ultan, Lloyd, 1929-1998 (University of Minnesota Press, 1977)
Music Theory was first published in 1977. This is a textbook for the study of music theory, using a historical approach which enables the student to learn about compositional devices as they appeared and evolved in early Western music. The textbook and its accompanying workbook provide for the study of basic analytical and compositional techniques through the use of selected literature and original compositional techniques through the use of selected literature and original compositional assignments. With these teaching materials techniques which have been employed periodically throughout hist.